GERAKAN ISLAM DI MALAYSIA: SEJARAH DAN TRADISI - Amir, Ahmad Nabil; Rahman, Tasnim Abdul; Aisyah, Aisyah (Faculty of Dakwah and Communication, UIN Syarif Hidayatullah Jakarta, 2024)
The paper discusses the historical origins of Islamic movement in Malaysia since colonial era. This was developed from two underlying bases; the ideal of reform and Islamic vision that was meant to bring about national consciousness and renewed aspiration of pan-Islamism designed under the powerful force of the Ottoman Caliphate. It analysed the impact of this awareness in inspiring the movement for reform and reassertion of Islamic spirit and unity following the rising tide of Islam in broad socio-political context. The essential role of Syed Syaikh al-Hadi, Dr. Burhanuddin al-Helmy, Ustaz Abu Bakar al-Baqir, and Syed Muhammad Naquib al-Attas has marked unprecedented influence in the meaningful struggle for religious and intellectual development. The movement bring forth critical value and ideal of Islam that espoused for progressive and rational spirit and reconstruction of ijtihad and dynamic activism, based on inclusive moral and ethical norm and standard. This study is based on qualitative method that focus on library research and content analysis. The data were collected from documentary study of primary and secondary sources, and technically analysed using interpretative, descriptive, historical and comparative method. The finding shows that the movement has brought about fundamental reform by introducing the principle values and ideals of Islam and its underlying doctrine of tawhid and unity and in projecting the idea of Islamization. It has bring certain impact in influencing the governmental policy and direction towards incorporating Islamic values and tradition in socio-political context and framework by taking account of the principle of maqasid syariah (the higher objective of Islamic law) and its application at every communal sector.